Kantian aesthetics : the problem of personal commitment, distinction, particularity, and comparison - Han, Li Qian (Nanyang Technological University, 2022)
Kant offers a paradoxical stance about aesthetics; judgements of the beautiful are subjective yet retains universal validity. Despite the plausibility of Kant’s account, this paper showcases four limitations and argues that we are unable to refute them. First, the problem of personal commitment suggests the infeasibility of appreciating art without some personal commitment towards artworks. Addressing this problem through free play is unsuccessful because it contradicts pre-established Kantian notions. Second, the problem of distinction arises due to dependent and free beauty functioning as two separate types of judgements as opposed to being under the same manifold. Defending Kant by interpreting dependent beauty as a sub-class of free beauty is futile because Kant did not characterise them as such. Third, the problem of particularity argues that Kant’s account is insufficient to prove that the same artwork must always produce the same aesthetic response in all individuals who encounter it under suitable circumstances. Attempting to resolve it through Anthony Savile’s account is unsuccessful because it undermines Kantian notions. Lastly, the problem of comparison highlights the inability of Kantian aesthetics to make meaningful comparative aesthetic judgements. Utilising Robert Burch’s solution is unsuccessful as it contradicts Kant’s ideal of beauty.